Method for producing (oxy) hydroxides and (oxy) hydroxides
By using a specific method to manufacture (oxygen) hydroxide electrode active materials for manganese and nickel in lithium-ion batteries, the problems of cycle life and voltage attenuation of existing materials are solved, achieving high volume energy density and longer battery life.
Patent Information
- Application Number
- CN202380059826.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-15
- Filing Date
- 2023-08-07
- Publication Date
- 2025-03-28
AI Technical Summary
The cycle life and voltage attenuation of existing lithium-ion battery cathode materials are limited, especially Mn-rich materials exhibit poor volume energy density.
A method is used to manufacture electrode active materials for electrochemical cell units with high volume energy density, including providing an aqueous solution of water-soluble salts of manganese and nickel and an aqueous solution of alkali metal hydroxide, combining within a specific pH range, precipitating the (oxygen) hydroxide of the transition metal using a coaxial mixer and recycling and drying.
Through the formation of spherical particles, the accumulation characteristics of the material are improved, thereby improving the volume energy density and extending the cycle life of the battery.
Smart Images

Figure BDA0005271792960000151 
Figure BDA0005271792960000161 
Figure BDA0005271792960000191
Abstract
Description
[0001] The present invention relates to a process for producing an (oxy)hydroxide of TM, wherein TM refers to a metal of which at least 97 mol-% is a transition metal, and wherein TM comprises manganese and nickel, and wherein at least 50 mol-% of TM is manganese, the process comprising the following steps
[0002] (a) providing an aqueous solution (α) of a water-soluble salt of at least one such metal and an aqueous solution (β) comprising an alkali metal hydroxide selected from the group consisting of NaOH and KOH,
[0003] (b) combining solutions (α) and (β) at a pH in the range of 9.5 to 10.3, wherein such step (b) is carried out using at least one coaxial mixer comprising two coaxially oriented conduits through which the aqueous solutions (β) and (α) are introduced into a stirred vessel, thereby causing the (oxy)hydroxide of TM to precipitate,
[0004] (c) recovering and drying the (oxy)hydroxide of said TM.
[0005] Lithiated transition metal oxides are currently used as electrode active materials for lithium-ion batteries. A great deal of research and development work has been done over the past few years to improve properties like charge density, specific energy, and also other properties (like cycle life reduction and capacity loss) that may adversely affect the life or applicability of lithium-ion batteries. Additional efforts have been made to improve manufacturing methods.
[0006] Many of the electrode active materials discussed today are of the lithiated nickel-cobalt-manganese oxide ("NCM material") or lithiated nickel-cobalt-aluminum oxide ("NCA material") type.
[0007] In a typical method for making cathode materials for lithium-ion batteries, a so-called precursor is first formed by coprecipitating a transition metal as a carbonate, an oxide or preferably an (oxy)hydroxide. The precursor is then mixed with a lithium compound (such as but not limited to LiOH, Li2O or Li2CO3) and calcined (fired) at a high temperature. One or more lithium compounds can be used as one or more hydrates or in a dehydrated form. Calcination (or firing) - also commonly referred to as thermal treatment or heat treatment of the precursor - is typically carried out at a temperature in the range of 600°C to 1,000°C. In the case of using hydroxides or carbonates as precursors, water or carbon dioxide is first removed, and then a lithiation reaction is carried out. The heat treatment is carried out in the heating zone of an oven or kiln.
[0008] A lot of research has been done to improve various properties of cathode active materials, such as energy density, charge and discharge performance such as capacity fade, etc. However, many cathode active materials suffer from limited cycle life and voltage fade. This is particularly true for many Mn-rich cathode active materials.
[0009] In EP 3 486 980, specific high manganese materials are disclosed with high energy density retention. However, the cathode active materials disclosed are also subject to limited energy density.
[0010] However, it has been observed that high manganese materials suffer from poor volumetric energy density.
[0011] It is therefore an object of the present invention to provide an electrochemical cell having a high volumetric energy density. Another object is to provide a method for producing an electrode active material for an electrochemical cell having a high volumetric energy density.
[0012] It has been found that volumetric energy density can be improved by spherical particles due to their enhanced packing properties compared to irregularly shaped particles.
[0013] It was found that the precursor of the cathode active material plays an important role, and therefore, a method for producing the (oxy)hydroxide as defined above was found, which method is hereinafter also referred to as "the method of the present invention" and "the method according to the (present) invention". The method of the present invention comprises steps (a) and (b) and (c), hereinafter also referred to as step (a) or simply (a), and step (b) or simply (b) or step (c) or simply (c). Steps (a) to (c) will be described in more detail below.
[0014] The process of the present invention is a process for precipitating an (oxy)hydroxide of a TM, wherein TM refers to a metal of which at least 97 mol-% is a transition metal, and wherein the TM comprises manganese and nickel, and wherein at least 50 mol-%, preferably 60 to 85 mol-%, of the TM is manganese. The TM may comprise a non-transition metal, such as aluminum or magnesium. More preferably, the TM is a combination of manganese and nickel.
[0015] The (oxy)hydroxide may be a stoichiometrically pure hydroxide or a hydroxide with anions other than hydroxide, such as carbonate or oxide ions. In the presence of an oxidizing agent, manganese in particular is easily oxidized. Carbonate may in particular be generated by adsorption of carbon dioxide, for example by alkali metal hydroxides or their aqueous solutions.
[0016] In one embodiment of the present invention, TM corresponds to the general formula (I)
[0017] Ni a M 1b Mn c (I)
[0018] These variables are defined as follows:
[0019] M 1 is at least one metal selected from the group consisting of Co, Ti, Zr, Nb, Ta, W, Sb, Sr, Al and Mg,
[0020] a is a number in the range of 0.20 to 0.50, preferably 0.30 to 0.40,
[0021] b is a number in the range of zero to 0.05, preferably zero or 0.02 to 0.04,
[0022] c is a number in the range of 0.50 to 0.80, preferably 0.60 to 0.70,
[0023] And a+b+c=1.0.
[0024] In one embodiment of the present invention, TM contains only Mn and Ni.
[0025] TM may contain trace amounts of additional metal ions as impurities, for example trace amounts of ubiquitous metals such as sodium, calcium or zinc, but such trace amounts will not be considered in the description of the present invention. Trace amounts in this context will mean amounts of 0.05 mol-% or less relative to the total metal content of the TM.
[0026] In one embodiment of the present invention, the (oxy)hydroxide of the obtained TM is in granular form and has a unimodal particle size distribution. The particle size distribution can be determined by light scattering or laser diffraction or electroacoustic spectroscopy, laser diffraction is preferred. The average particle size (D50) is preferably in the range of 2 to 15 μm, for example 2 to 12 μm, and in a preferred embodiment, the average particle size D50 is in the range of 3 to 8 μm.
[0027] In step (a), an aqueous solution (α) of at least one water-soluble salt of such metal and an aqueous solution (β) containing an alkali metal hydroxide selected from NaOH and KOH are provided. Two or more aqueous solutions (α) may be provided, each of which contains a water-soluble salt. However, it is preferred that only one solution (α) is provided.
[0028] The term water-soluble salt of nickel or manganese or a metal other than nickel and manganese refers to a salt which exhibits a solubility of 25 g / l or more in distilled water at 25° C., the amount of salt being determined ignoring water of crystallization and water from aquo complexes. The water-soluble salt of nickel and manganese may preferably be Ni 2+ and Mn 2+Examples of water-soluble nickel and manganese salts are sulfates, nitrates, acetates and halides, especially chlorides. Preferred are nitrates and sulfates, with sulfates being more preferred.
[0029] The aqueous solution (a) preferably contains Ni and Mn and optionally one or more further metals in relative concentrations of the TMs intended as precursors.
[0030] The one or more solutions (a) may have a pH value in the range of 2 to 5. In embodiments where a higher pH value is desired, ammonia may be added to the solution (a). However, it is preferred not to add ammonia to the solution (a).
[0031] In one embodiment of the present invention, a solution (α) is provided, which contains all the metals to be precipitated.
[0032] Furthermore, an aqueous solution of an alkali metal hydroxide is provided in step (a), hereinafter also referred to as solution (β). Examples of alkali metal hydroxides are lithium hydroxide, preferably potassium hydroxide and a combination of sodium hydroxide and potassium hydroxide, and even more preferably sodium hydroxide.
[0033] The solution (β) may contain a certain amount (eg 0.1 to 2% by weight relative to the corresponding amount of alkali metal hydroxide) of carbonate added intentionally or by aging the solution or the corresponding alkali metal hydroxide.
[0034] The solution (β) may have a hydroxide concentration in the range of 0.1 to 12 mol / l, preferably 6 to 10 mol / l.
[0035] The pH value of the solution (β) is preferably 13 or higher, for example 14.5.
[0036] In the process of the invention, preference is given to using ammonia, but feeding it separately as solution (γ) or in solution (β) instead of in solution (α).
[0037] Optionally, at least one complexing agent selected from ammonia, glycine, citrate and oxalate may be provided. Glycine, citrate and oxalate are preferably provided as sodium salts. The complexing agent may be contained in the aqueous solution (β) or in a separate aqueous solution (γ).
[0038] However, it is more preferred to carry out the process of the invention without the use of a complexing agent.
[0039] The aqueous solution (γ) may contain ammonia in the range of 1 to 25% by weight.
[0040] The aqueous solution (γ) may contain glycine, citrate or oxalate as a salt (eg as a sodium salt) in the range of 0.1% to 5% by weight. In each of these cases, the percentages refer to the free acid.
[0041] In step (b) of the process according to the invention, the aqueous solutions (α) and (β) are combined at a pH value in the range of 9.5 to 10.3, preferably 9.5 to 10.0, wherein step (b) is carried out using at least one coaxial mixer comprising two coaxially oriented conduits through which the aqueous solution (β) and the aqueous solution (α) are introduced into the stirred vessel. The pH value refers to the value measured at 23°C.
[0042] During step (b), care is taken to achieve a minimum pH value of 9.5. Furthermore, during step (b), care is taken not to exceed a pH value of 10.3. Preferably, the pH value is kept constant at a value within the range of 10.0 to 10.3 (± 0.01).
[0043] In the context of the present invention, the coaxial mixer comprises two coaxially arranged pipes, through which the aqueous solution (β) and the aqueous solution (α) are introduced into the stirred vessel. In one embodiment of the present invention, the introducing step is performed by using two or more coaxial mixers, through which the aqueous solution (β) and the aqueous solution (α) are introduced into the stirred vessel. In another embodiment of the present invention, the introducing step is performed by using only one coaxially arranged pipe system, through which the aqueous solution (β) and the aqueous solution (α) are introduced into the stirred vessel.
[0044] In a preferred embodiment of the present invention, the aqueous solution (α) is introduced through the inner pipe of the coaxial mixer and the aqueous solution (β) is introduced through the outer pipe, which will result in a slight degree of scaling.
[0045] In one embodiment of the invention, the inner conduit of the coaxial mixer has an inner diameter in the range of 1 mm to 120 mm, preferably in the range of 5 mm to 50 mm, depending on the container size. The larger the container, the larger the diameter of the inlet tip.
[0046] In one embodiment of the present invention, the outer pipe of such a coaxial mixer has an inner diameter in the range of 1.5 to 10 times, preferably 1.5 to 6 times, the inner diameter of the inner pipe.
[0047] The duct preferably has a circular cross-section.
[0048] In one embodiment of the invention, the conduit wall has a thickness in the range of 1 to 10 mm.
[0049] The pipe may be made of steel, stainless steel, or steel coated with PTFE (polytetrafluoroethylene), FEP (fluorinated ethylene-propylene copolymer), or PFA (perfluoroalkoxy polymer), preferably stainless steel.
[0050] In one embodiment of the present invention, the conduit of the coaxial mixer is curved. In a preferred embodiment of the present invention, the conduit of the coaxial mixer is non-curved.
[0051] The coaxial mixer may act as a coaxial nozzle.
[0052] In one embodiment of the present invention, the introduction position of the aqueous solution (α) and (β) is higher than the liquid level, for example, 3 to 50 cm higher. In a preferred embodiment of the present invention, the introduction position of the aqueous solution of the transition metal salt and the alkali metal hydroxide is lower than the liquid level, for example, 5 to 250 cm lower, preferably lower than 10 cm up to 200 cm.
[0053] If an aqueous solution (γ) is also introduced, this aqueous solution (γ) is also preferably introduced via the coaxial mixer.
[0054] In one embodiment of the present invention, step (b) is carried out at a temperature ranging from 5°C to 75°C, preferably from 35°C to 70°C.
[0055] The pressure conditions used for step (b) are generally not critical.Step (b) can be carried out at ambient pressure or at slightly elevated pressure, for example at a pressure in the range of 5 mbar to 5 bar above ambient pressure.
[0056] In one embodiment of the present invention, the residence time of step (b) is in the range of 10 minutes to 12 hours.
[0057] Step (b) may be performed continuously or as a batch process. In one embodiment, step (b) is performed as a batch process and the mother liquor is removed (discharged) by a solid-liquid separation device (eg, a clarifier, such as a lamella clarifier).
[0058] In one embodiment of the present invention, the container is a continuous stirred tank reactor. The continuous stirred tank reactor is advantageously equipped with a device for controlling the temperature and devices such as baffles, guide vanes, etc.
[0059] Step (b) is preferably carried out in the absence of an oxidizing agent like oxygen. For this purpose, step (b) can be carried out under an inert atmosphere such as nitrogen or a noble gas such as argon.
[0060] Preferably, step (b) is performed under mixing (eg stirring).In one embodiment, a stirring energy input in the range of 2.0 to 25.0 W / l is introduced.
[0061] During step (b), a slurry of the (oxy)hydroxide of TM is formed. In order to increase the capacity of the stirred reactor, the mother liquor can be removed during step (b), for example by means of a clarifier. In this context, the mother liquor refers to water containing, for example, the corresponding alkali metal salt of the counterion of TM, a complexing agent (if applicable) and traces of alkali metal hydroxide.
[0062] After step (b) has been carried out, step (c) is carried out,
[0063] (c) recovering and drying the (oxy)hydroxide of said TM.
[0064] Step (c) preferably comprises a solid-liquid separation step, for example using a centrifuge or by filtration, for example using a belt filter or a filter press. By means of said solid-liquid separation step, the liquid phase ("mother liquor") is removed and the particulate hydroxide is recovered.
[0065] The filtration step preferably comprises one or more washing steps. The filter cake can be washed with water or with an aqueous solution of NaOH or KOH, such as the diluted solution (β). A solid residue and a mother liquor, such as a filtrate, are obtained.
[0066] After the (oxy)hydroxide of the TM has been recovered, the resulting solid residue may be dried, for example at a temperature in the range of 80° C. to 120° C. The drying may be carried out in vacuum, under an inert gas such as nitrogen, or in air. In embodiments where the residue is dried under air, at least partial oxidation of the manganese may occur, and part of the hydroxide may be converted to the oxide. Preferably, most of the manganese is converted to an oxidation state of +IV.
[0067] In one embodiment of the present invention, after step (b), a sub-step (b+) is carried out, wherein the slurry from step (b) is transferred to a second stirred vessel, in which it is combined with solutions (α) and (β) at a pH value in the range of 9.5 to 11.0 measured at 23°C, wherein step (b+) is carried out in a continuous or batch or semi-continuous process, thereby further growing the particles of the (oxy)hydroxide of TM.
[0068] The temperature conditions and the general definition of solutions (α) and (β) are as described above in step (b).
[0069] In one embodiment of the invention, step (b+) has a duration in the range of 1 to 10 hours.
[0070] A granular hydroxide is obtained, which is an excellent precursor for a cathode active material. The precursor can be mixed with a lithium compound, such as LiOH or Li2CO3 or Li2O2, and optionally, with one or more additives such as Al2O3, TiO2, ZrO2, Zr(OH)4 or oxyhydroxides of Al, Ti or Zr, and then heat-treated at a temperature in the range of 800 °C to 1000 °C. The molar ratio Li:TM is preferably in the range of 1.05:1 to 1.5:1, preferably 1.25 to 1.4.
[0071] Another aspect of the invention relates to a precursor for a cathode active material for a lithium-ion battery. The precursor is also hereinafter referred to as the precursor of the invention or the (oxy)hydroxide of the invention. The precursor of the invention is in the form of a granular (oxy)hydroxide of TM, where TM refers to a metal in which at least 97 mol-% is a transition metal, and where TM contains manganese and nickel, and where at least 50 mol-% of TM is manganese,
[0072] 0 ≤ x < 1, 1 < y ≤ 2, and 0 ≤ t ≤ 0.1,
[0073] wherein the granular transition metal (oxy)hydroxide has an average secondary particle diameter D50 in the range of 2 to 15, preferably 3 to 8 μm,
[0074] and wherein such secondary particles are aggregated from primary particles with a substantially radial orientation.
[0075] "Substantially radial orientation" does not require a perfect radial orientation, but includes a deviation from a perfect radial orientation of at most 5 degrees in SEM analysis.
[0076] Furthermore, at least 60% of the secondary particle volume is filled with radially oriented primary particles. Preferably, only a smaller inner part of those particle volumes, such as at most 40%, preferably at most 20%, is filled with non-radially oriented primary particles, such as randomly oriented primary particles.
[0077] Preferably, the precursor of the invention shows reflections at 8.6° to 9.0° (a), 16.00° to 18.00° (b) and 21.40° to 22.00° 2θ (c) in X-ray diffraction analysis recorded with Cu-Kα-radiation.
[0078] Preferred is a granular metal (oxy)hydroxide according to general formula (II)
[0079] TMO x (OH) y (CO3) t (II)
[0080] Preferably, TM corresponds to formula (I)
[0081] Ni a M 1 b Mn c …………………………(I)
[0082] These variables are defined as follows:
[0083] M 1 is at least one metal selected from the group consisting of Co, Ti, Zr, Nb, Ta, W, Sb, Sr, Al and Mg,
[0084] a is a number in the range of 0.20 to 0.50, preferably 0.30 to 0.40,
[0085] b is a number in the range of zero to 0.05, preferably zero or 0.02 to 0.04,
[0086] c is a number in the range of 0.50 to 0.80, preferably 0.60 to 0.70,
[0087] And a+b+c=1.0.
[0088] In one embodiment of the present invention, TM contains only Mn and Ni.
[0089] In one embodiment of the present invention, the (oxy)hydroxide of the present invention has a relative humidity of 2 to 50 m / s, determined by nitrogen adsorption according to DIN-ISO 9277:2003-05 after degassing at 120° C. for one hour. 2 The specific surface area according to BET is in the range of 1.1767 W / g.
[0090] In one embodiment of the present invention, the particle size distribution [(D90)-(D10)] of the (oxy)hydroxide of the present invention divided by (D50) is in the range of 0.3 to 2, preferably 0.5 to 1.0.
[0091] In one embodiment of the invention, the average shape factor of the secondary particles of the (oxy)hydroxide of the invention is higher than 0.80, preferably at least 0.85, when measured by scanning electron microscopy ("SEM") imaging at 1000× magnification. The upper limit is 1.0, or at least up to 0.98. For the imaging, a representative sample of 100 particles is analyzed. The shape factor of a single particle is calculated from the perimeter and area measured from the top view SEM image:
[0092] Shape factor = (4π·area) / (perimeter) 2
[0093] While a perfect sphere would have a shape factor of 1.0, any deviation from perfect sphericity results in a shape factor < 1.0.
[0094] The average shape factor is then determined by averaging at least 30, for example 30 to 40 particles.
[0095] Another aspect of the present invention relates to the use of the precursor of the present invention for the production of a cathode active material for a lithium ion battery. Another aspect of the present invention relates to a method for producing a cathode active material for a lithium ion battery, wherein the method comprises the following steps:
[0096] (1) mixing at least one precursor according to the invention with at least one lithium compound selected from lithium hydroxide, lithium carbonate and lithium peroxide and optionally at least one oxide or (oxy)hydroxide or sulfate of Mg, Al, Ti, Zr, Nb, Ta, W or Mo, and
[0097] (2) The mixture obtained in step (1) is heated to 800°C to 1000°C, preferably 850°C to 970°C.
[0098] Examples of suitable oxides or (oxy)hydroxides or sulfates of Mg, Al, Ti, Zr, Nb, Ta, W or Mo are MgO, Mg(OH)2, MgSO4, AlOOH, Al(OH)3, Al2O3, Al2(SO4)3, TiO(OH)2, TiO2, TiOSO4, Ti(OH)4, TiO2·aq, Zr(OH)4, ZrO(OH)2, ZrO2, ZrOSO4, ZrO2·aq, Nb2O5, niobic acid, Ta2O5, WO3, MoO3, and combinations of at least two of the foregoing.
[0099] The stoichiometric ratio of lithium to TM is preferably such that lithium exceeds the metal from the TM.
[0100] The heating in step (2) can be carried out in a kiln (eg, a rotary kiln, a roller kiln or a pusher kiln).
[0101] The duration of step (2) may be in the range of 3 to 24 hours, preferably 4 to 12 hours.
[0102] In one embodiment of the present invention, the temperature is gradually increased and then reaches the desired temperature of 800° C. to 1000° C., preferably 850° C. to 970° C. For example, the mixture of step (1) is first heated to a temperature of 250° C. to 350° C., and then kept constant for a period of 10 min to 4 hours, and then it is increased to 400° C. to 550° C. and kept constant for a period of 10 min to 4 hours, and then it is increased to 800° C. to 1000° C., preferably 850° C. to 970° C.
[0103] In one embodiment of the present invention, the heating rate in step (2) is in the range of 0.1 to 10° C. / min.
[0104] In one embodiment of the present invention, after step (2), a post-treatment is carried out, which is referred to as step (3) hereinafter, and the post-treatment is carried out, for example, with water, an aqueous solution of aluminum sulfate or magnesium sulfate or titanium sulfate or zirconium sulfate or sulfuric acid, or a combination of sulfuric acid and aluminum sulfate or titanium sulfate or magnesium sulfate. After such treatment, another heating treatment step, for example at 300° C. to 600° C., is preferably carried out.
[0105] In one embodiment of the present invention, the treatment is carried out with a solution of a compound of Mg, Al, Ti or Zr in an inorganic acid (eg a solution of Al2(SO4)3 in aqueous H2SO4).
[0106] The treatment in step (3) can be carried out by adding a solution of an inorganic acid or a compound of Mg, Al, Ti or Zr to the cathode active material of step (2) and allowing the resulting mixture to interact. This interaction can be enhanced by stirring.
[0107] In one embodiment of the present invention, step (3) is carried out at a temperature in the range of 5° C. to 85° C., preferably 10° C. to 60° C. Ambient temperature is particularly preferred.
[0108] In one embodiment of the present invention, step (3) is carried out at normal pressure. However, it is preferred that step (3) is carried out at elevated pressure (e.g., 10 mbar to 10 bar above normal pressure) or by suction (e.g., 50 to 250 mbar below normal pressure, preferably 100 to 200 mbar below normal pressure).
[0109] In one embodiment of the present invention, step (3) is performed in a filter device with a stirrer, such as a pressure filter with a stirrer or a suction filter with a stirrer.
[0110] The duration of treatment of the material obtained from step (2) with the compound of Mg, Nb, W, Al, Ti or Zr may be in the range of 2 to 60 minutes, preferably 10 to 45 minutes.
[0111] In one embodiment of the present invention, the volume ratio of the material obtained from step (2) to the solution of the inorganic acid or the compound of Mg, Nb, W, Al, Ti or Zr is in the range of 1:1 to 1:10, preferably 1:1 to 1:5.
[0112] In one embodiment of the present invention, step (3) is repeated, for example, once to 10 times. In a preferred embodiment, step (3) is performed only once.
[0113] Another aspect of the present invention relates to a cathode active material, hereinafter also referred to as the cathode active material of the present invention. The cathode active material of the present invention is according to the general formula Li 1+k TM 1-k A granular material of O2, wherein k is in the range of 0.1 to 0.3, and wherein TM refers to a combination of metals of which at least 97 mol-% are transition metals, and wherein TM comprises manganese and nickel, and wherein at least 50 mol-% of TM is manganese,
[0114] wherein the particulate cathode active material has an average secondary particle diameter D50 in the range of 2 to 15 μm, preferably 3 to 8 μm,
[0115] And wherein such secondary particles are aggregated from substantially radially oriented primary particles, and wherein the secondary particles have an average shape factor higher than 0.80, preferably at least 0.85, when measured by SEM imaging at 1000× magnification.
[0116] "Substantially radial orientation" does not require perfect radial orientation, but includes deviations from perfect radial orientation of up to 5 degrees in SEM analysis.
[0117] Furthermore, at least 60% of the secondary particle volume is filled with radially oriented primary particles. Preferably, only a smaller inner portion of the volume of those particles, e.g. up to 40%, preferably up to 20%, is filled with non-radially oriented primary particles, e.g. randomly oriented primary particles.
[0118] In one embodiment of the present invention, TM corresponds to the general formula (I)
[0119] Ni a M 1 b Mn c (I)
[0120] These variables are defined as follows:
[0121] M 1 is at least one metal selected from the group consisting of Co, Ti, Zr, Nb, Ta, W, Sb, Sr, Al and Mg,
[0122] a is a number in the range of 0.20 to 0.50, preferably 0.30 to 0.40,
[0123] b is a number in the range of zero to 0.05, preferably zero or 0.02 to 0.04,
[0124] c is a number in the range of 0.50 to 0.80, preferably 0.60 to 0.70,
[0125] And a+b+c=1.0.
[0126] In one embodiment of the present invention, TM contains only Mn and Ni.
[0127] In one embodiment of the present invention, the cathode active material of the present invention comprises secondary particles, which comprise a Li 1+k TM 1-k O2 primary particles, these secondary particles are coated with at least one oxide compound of Nb, W, Ti or Zr (preferably Nb, Ti or Zr).
[0128] Another aspect of the present invention relates to an electrode comprising at least one electrode active material according to the present invention. They can be used in particular in lithium ion batteries. A lithium ion battery comprising at least one electrode according to the present invention exhibits good discharge behavior. An electrode comprising at least one electrode active material according to the present invention is hereinafter also referred to as a cathode according to the present invention or a cathode according to the present invention.
[0129] Specifically, the cathode of the present invention contains
[0130] (A) at least one cathode active material according to the present invention,
[0131] (B) carbon in an electrically conductive form,
[0132] (C) a binder polymer, also referred to as a binder or binder (C), and, preferably,
[0133] (D) Current collector.
[0134] In a preferred embodiment, the cathode of the present invention comprises
[0135] (A) 80 to 98% by weight of the cathode active material of the present invention,
[0136] (B) 1 to 17% by weight of carbon,
[0137] (C) 1 to 15% by weight of a binder polymer,
[0138] Percentages are relative to the sum of (A), (B), and (C).
[0139] The cathodes according to the present invention may comprise additional components. They may include a current collector such as, but not limited to, aluminum foil. They may further comprise conductive carbon and a binder.
[0140] The cathode according to the present invention contains conductive modified carbon, also referred to as carbon (B) for short. Carbon (B) may be selected from soot, activated carbon, carbon nanotubes, graphene and graphite, and a combination of at least two of the foregoing.
[0141] Suitable binders (C) are preferably selected from organic (co)polymers. Suitable (co)polymers, i.e. homopolymers or copolymers, can be selected from (co)polymers obtainable, for example, by anionic, catalytic or free radical (co)polymerization, in particular from polyethylene, polyacrylonitrile, polybutadiene, polystyrene, and copolymers of at least two comonomers selected from ethylene, propylene, styrene, (meth)acrylonitrile and 1,3-butadiene. Polypropylene is also suitable. In addition, polyisoprene and polyacrylates are also suitable. Polyacrylonitrile is particularly preferred.
[0142] In the context of the present invention, polyacrylonitrile is understood to mean not only polyacrylonitrile homopolymers but also copolymers of acrylonitrile with 1,3-butadiene or styrene. Polyacrylonitrile homopolymers are preferred.
[0143] In the context of the present invention, polyethylene is understood to mean not only homopolyethylene but also copolymers of ethylene which comprise at least 50 mol-% of copolymerized ethylene and up to 50 mol-% of at least one further comonomer, for example α-olefins such as propylene, butene (1-butene), 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-pentene and also isobutene, vinylaromatic compounds such as styrene and also (meth)acrylic acid, vinyl acetate, vinyl propionate, C1-C12-hydroxyethyl esters of (meth)acrylic acid. 10 - Alkyl esters are especially methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, and also maleic acid, maleic anhydride and itaconic anhydride. The polyethylene may be HDPE or LDPE.
[0144] In the context of the present invention, polypropylene is understood to mean not only homopolypropylene, but also copolymers of propylene comprising at least 50 mol-% copolymerized polypropylene and up to 50 mol-% of at least one further comonomer, for example ethylene and α-olefins such as butene, 1-hexene, 1-octene, 1-decene, 1-dodecene and 1-pentene. The polypropylene is preferably isotactic or substantially isotactic.
[0145] In the context of the present invention, polystyrene is understood to mean not only homopolymers of styrene but also C1-C12 copolymers with acrylonitrile, 1,3-butadiene, (meth)acrylic acid, (meth)acrylic acid, and the like. 10 - copolymers of alkyl esters, divinylbenzene, especially 1,3-divinylbenzene, 1,2-diphenylethylene and α-methylstyrene.
[0146] Another preferred binder (C) is polybutadiene.
[0147] Other suitable binders (C) are selected from polyethylene oxide (PEO), cellulose, carboxymethylcellulose, polyimide and polyvinyl alcohol.
[0148] In one embodiment of the present invention, the binder (C) is selected from a group consisting of binders having an average molecular weight M in the range of 50,000 to 1,000,000 g / mol, preferably to 500,000 g / mol. w Those (co)polymers.
[0149] The binder (C) may be selected from crosslinked or non-crosslinked (co)polymers.
[0150] In a particularly preferred embodiment of the present invention, binder (C) is selected from halogenated (co) polymers, especially fluorinated (co) polymers. Halogenated or fluorinated (co) polymers are understood to mean those (co) polymers comprising at least one (co) polymerized (co) monomer having at least one halogen atom or at least one fluorine atom per molecule, more preferably at least two halogen atoms or at least two fluorine atoms per molecule. Examples are polyvinyl chloride, polyvinylidene chloride, polytetrafluoroethylene, polyvinylidene fluoride (PVdF), tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), vinylidene fluoride-tetrafluoroethylene copolymer, perfluoroalkyl vinyl ether copolymer, ethylene-tetrafluoroethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer and ethylene-chlorofluoroethylene copolymer.
[0151] Suitable binders (C) are, in particular, polyvinyl alcohols and halogenated (co)polymers, for example polyvinyl chloride or polyvinylidene chloride, and in particular fluorinated (co)polymers, such as polyvinyl fluoride and in particular polyvinylidene fluoride and polytetrafluoroethylene.
[0152] The cathode of the present invention may contain 1% to 15% by weight of one or more binders relative to the electrode active material. In other embodiments, the cathode of the present invention may contain 0.1% to less than 1% by weight of one or more binders.
[0153] Another aspect of the present invention is a battery comprising at least one cathode comprising the electrode active material of the present invention, carbon and a binder, at least one anode, and at least one electrolyte.
[0154] The embodiments of the cathode of the present invention have been described above in detail.
[0155] The anode may contain at least one anode active material, such as carbon (graphite), TiO2, lithium titanium oxide, silicon or tin. The anode may additionally contain a current collector, such as a metal foil such as copper foil.
[0156] The electrolyte may include at least one non-aqueous solvent, at least one electrolyte salt, and optionally additives.
[0157] The nonaqueous solvent of the electrolyte may be liquid or solid at room temperature and is preferably selected from polymers, cyclic or acyclic ethers, cyclic or acyclic acetals, and cyclic or acyclic organic carbonates.
[0158] Examples of suitable polymers are in particular polyalkylene glycols, preferably poly-C1-C4-alkylene glycols, and in particular polyethylene glycol. Polyethylene glycol may account for up to 20 mol% of one or more C1-C4-alkylene glycols. Polyalkylene glycols are preferably polyalkylene glycols with two methyl or ethyl end caps.
[0159] The molecular weight M of suitable polyalkylene glycols and in particular suitable polyethylene glycols is w It may be at least 400 g / mol.
[0160] The molecular weight M of suitable polyalkylene glycols and in particular suitable polyethylene glycols is w It may be up to 5 000 000 g / mol, preferably up to 2 000 000 g / mol.
[0161] Examples of suitable acyclic ethers are, for example, diisopropyl ether, di-n-butyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, of which 1,2-dimethoxyethane is preferred.
[0162] Examples of suitable cyclic ethers are tetrahydrofuran and 1,4-dioxane.
[0163] Examples of suitable acyclic acetals are, for example, dimethoxymethane, diethoxymethane, 1,1-dimethoxyethane and 1,1-diethoxyethane.
[0164] Examples of suitable cyclic acetals are 1,3-dioxane and in particular 1,3-dioxolane.
[0165] Examples of suitable acyclic organic carbonates are dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate.
[0166] Examples of suitable cyclic organic carbonates are compounds according to the general formula (III) and (IV)
[0167]
[0168] Where R 1 , R 2 and R 3 may be identical or different and are selected from hydrogen and C1-C4-alkyl, for example methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl, wherein R 2 and R 3 Preferably not all are tert-butyl.
[0169] In a particularly preferred embodiment, R 1 is methyl and R 2 and R 3 Each is hydrogen, or R 1 , R 2 and R 3 In another embodiment, R 1 is fluorine and R 2 and R 3 Each is hydrogen.
[0170] Another preferred cyclic organic carbonate is vinylene carbonate, formula (V).
[0171]
[0172] The solvent(s) are preferably used in anhydrous state, ie with a water content in the range from 1 ppm to 0.1% by weight, which water content can be determined, for example, by Karl-Fischer titration.
[0173] The electrolyte further comprises at least one electrolyte salt. Suitable electrolyte salts are in particular lithium salts. Examples of suitable lithium salts are LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiC(C n F 2n+1 SO2)3, lithium imide such as LiN(C n F 2n+ 1SO2)2, wherein n is an integer in the range of 1 to 20, LiN(SO2F)2, Li2SiF6, LiSbF6, LiAlCl4 and n F 2n+1 SO2) t Salts of YLi, wherein m is defined as follows:
[0174] When Y is selected from oxygen and sulfur, t=1,
[0175] When Y is selected from nitrogen and phosphorus, t=2, and
[0176] When Y is selected from carbon and silicon, t=3.
[0177] Preferred electrolyte salts are selected from LiC(CF3SO2)3, LiN(CF3SO2)2, LiPF6, LiBF4, LiClO4, among which LiPF6 and LiN(CF3SO2)2 are particularly preferred.
[0178] In one embodiment of the invention, the battery according to the invention comprises one or more separators by which the electrodes are mechanically separated. Suitable separators are polymer films, in particular porous polymer films, which are non-reactive to metallic lithium. Particularly suitable materials for separators are polyolefins, in particular film-forming porous polyethylene and film-forming porous polypropylene.
[0179] The membrane composed of polyolefin, in particular polyethylene or polypropylene, can have a porosity in the range of 35% to 45%. Suitable pore diameters are, for example, in the range of 30 to 500 nm.
[0180] In another embodiment of the present invention, the separator can be selected from a PET nonwoven material filled with inorganic particles. Such a separator can have a porosity in the range of 40% to 55%. Suitable pore sizes are, for example, in the range of 80 to 750 nm.
[0181] The battery according to the invention further comprises a housing, which may have any shape, for example cubic or in the shape of a cylindrical disk or cylindrical can. In one variant, a metal foil configured as a pouch is used as housing.
[0182] The battery according to the invention shows good discharge behavior, for example very good discharge and cycling behavior at low temperatures (0° C. or lower, for example down to −10° C. or even lower).
[0183] The battery according to the invention may comprise two or more electrochemical cells combined with one another, which may be connected in series or in parallel, for example. Preferably they are connected in series. In the battery according to the invention, at least one of the electrochemical cells comprises at least one cathode according to the invention. Preferably, in the electrochemical cells according to the invention, the majority of the electrochemical cells comprise a cathode according to the invention. Even more preferably, in the battery according to the invention, all electrochemical cells comprise a cathode according to the invention.
[0184] The invention further provides for the use of a battery according to the invention in an apparatus, in particular in a mobile apparatus. Examples of mobile apparatuses are vehicles, such as cars, bicycles, aircraft or water vehicles such as boats or ships. Other examples of mobile apparatuses are those that are moved manually, such as computers (especially laptops), telephones, or electric hand tools (for example in the construction industry), in particular drills, battery-powered screwdrivers or battery-powered staplers.
[0185] The present invention is further illustrated by working examples. Description of the drawings:
[0186] Figure 1 Top view SEM images of the inventive precursors TM-OH.1 (a, b) and TM-OH.2 (c, d) are shown. Top view SEM images of the comparative precursor C-TM-OH.3 are shown in panels (e) and (f).
[0187] For the determination of the particle size, a Mastersizer 3000 from Malvern Panalytical GmbH was used. The sample was filled into the device until a light obscuration of between 4.0% and 14.0% was reached. The corresponding volume-based particle size distribution (PSD) was determined by laser diffraction based on Mie's scattering theory. The refractive index of H2O (as dispersant) was chosen to be 1.33, while the refractive index of the solid phase was chosen to be 2.19.
[0188] I. Preparation of Precursor TM-OH
[0189] Manufacturing example, general comments:
[0190] During all precipitation experiments the stirred vessel had a constant nitrogen flooding. The pH values refer to measurements at 23°C.
[0191] Aqueous solution (α.1): NiSO4 and MnSO4 (1:2 molar ratio), with a total TM concentration of 1.65 mol / kg
[0192] Aqueous solution (β.1): NaOH aqueous solution (25wt%)
[0193] I.1 Preparation of the Precursor TM-OH.1 of the Invention
[0194] The precursor TM-OH.1 of the invention was prepared in a 2.4 L stirred vessel using a dosing unit comprising a coaxial mixer. In addition, the stirred vessel comprised an overflow system and a clarifier. The stirrer consisted of a stirring shaft equipped with two four-bladed pitched-paddle impellers. The stirred vessel was filled with 2 L of deionized water and the temperature was set to 55° C. under constant stirring, with an energy absorption of (ε 平均值 About 6.3W / L).
[0195] The aqueous solutions (α.1) and (β.1) are introduced into a stirred vessel through a coaxial mixer. The formation of a slurry is observed. The total volume flow of the solutions (α.1) and (β.1) is adjusted to result in an average residence time of 5 h. During the reaction, the pH value is set to 10.0 and kept constant by a pH regulating loop that adjusts the volume flow of the solution (β.1). The precipitation reaction is carried out in a continuous mode with a mother liquor discharge rate of 35% (discharged through a clarifier relative to the total volume flow). The resulting slurry is collected by overflow. The collected slurry contains about 400 g / L of TM-OH.1. TM-OH.1 is collected by filtration and washed with a solution (β.1) (1 kg solution (β.1) / kg solid TM-OH.1) and deionized water. Then, TM-OH.1 is dried at 120°C for 14 hours.
[0196] I.2 Preparation of the Precursor TM-OH.2 of the Invention
[0197] Example I.1 was repeated, except that no mother liquor was discharged via the clarifier and the stirring energy input was set to ≈5.4 W / L. The slurry discharged via the overflow system contained 120 g / l solids. TM-OH.2 was obtained.
[0198] I.3 Preparation of comparative precursor C-TM-OH.3
[0199] The manufacture of C-TM-OH.3 was carried out in a 30 L stirred vessel without a coaxial mixer. The agitator consisted of a stirring shaft equipped with two four-blade pitched impellers. The aqueous solutions (α.1) and (β.1) were introduced into the stirred vessel through separate dosing pipes. The formation of a slurry was observed. The total volume flow of solutions (α.1) and (β.1) was adjusted to result in an average residence time of 12 h. The pH value was set to 11.5 and kept constant by a pH regulating circuit that adjusted the volume flow of solution (β.1).
[0200] The slurry discharged through the overflow system contained 120 g / l solids. C-TM-OH.3 was collected by filtration and washed with solution (β.1) (1 kg solution (β.1) / kg solid C-TM-OH.3.) and deionized water. C-TM-OH.3 was then dried at 120°C for 14 hours.
[0201] The SEM images of the obtained precursors TM-OH.1, TM-OH.2 and C-TM-OH.3 are shown in Figure 1 and another cross section is shown in Figure 2 middle.
[0202] Table 1: Summary of physical properties of inventive and comparative precursors
[0203]
[0204] nd: not determined
[0205] II. Synthesis of cathode active materials from inventive and comparative precursors
[0206] II.1 Synthesis of cathode active materials CAM.1 and CAM.2 from the precursors TM-OH.1 and TM-OH.2 of the invention
[0207] The corresponding cathode active material is synthesized from the precursor TM-OH.1 or TM-OH.2 of the present invention by mixing the dried precursor with Li2CO3 and each 0.1 mol-% Zr(OH)4 and TiO2 (relative to the sum of Mn and Ni) in a molar ratio Li:(Ni+Mn+Ti+Zr) of 1.36:1. The resulting mixture is then filled into a crucible and heated at 1.5°C / min up to 950°C and kept at this temperature for 5 hours. Thereafter, the cathode active material obtained is cooled to room temperature and sieved using a 32 μm sieve, and then a post-treatment is applied. A calcined material is obtained.
[0208] For the purpose of post-treatment, the corresponding calcined material was treated with a mixture of aqueous H2SO4 solution and Al2(SO4)3. 100 g of water, 200 g of 0.4 M H2SO4 and 37 μmol Al2(SO4)3 were added to 100 g of the corresponding calcined material and stirred for 30 min. After filtration, the CAM was washed with a washing medium (water: calcined material was 4:1), filtered and dried under vacuum. Finally, the material treated in this way was annealed again at 400°C with a heating ramp of 3°C / min for 5 hours to obtain CAM.1 or CAM.2, respectively. A cross-sectional SEM image of CAM.1 is shown in Figure 3 middle.
[0209] II.2. Synthesis of comparative cathode materials from comparative precursor C-TM-OH.3
[0210] Comparative cathode active material C-CAM.3 was synthesized from the inventive precursor C-TM-OH.3 by mixing the dried precursor with Li2CO3, each 0.1 mol-% Zr(OH)4 and TiO2 (relative to the sum of Mn and Ni) in a molar ratio Li:(Ni+Mn+Ti+Zr) of 1.36:1. The resulting mixture was then filled into a crucible and heated at 1.5°C / min up to 950°C and kept at this temperature for 6h. Thereafter, the calcined material obtained was cooled to room temperature and sieved using a 32 μm sieve, and then post-treatment was applied.
[0211] For the purpose of post-treatment, the calcined material was treated with a mixture of aqueous H2SO4 solution and Al2(SO4)3. 100 g of water, 200 g of 0.4 M H2SO4 and 37 μmol Al2(SO4)3 were added to 100 g of the comparative calcined material and stirred for 30 min. After filtration, the CAM was washed with a washing medium (water: calcined material = 4:1), filtered and dried under vacuum. Finally, the material treated in this way was annealed again at 400°C with a heating ramp of 3°C / min for 5 hours, resulting in the comparative cathode active material C-CAM.3.
[0212] Table 2: Summary of the physical properties of the resulting CAMs
[0213]
[0214]
[0215] The compacted density is measured at a pressure of 250 MPa.
[0216] III. Preparation of electrodes, electrolytes and electrochemical evaluation of the inventive and comparative cathode active materials
[0217] III.1 Electrode preparation
[0218] Electrodes with the following composition were prepared by dissolving the binder in N-methyl-2-pyrrolidone and adding a conductive agent: 94% cathode active material (CAM), 3% conductive agent (Super C65) and 3% polymer binder (polyvinylidene fluoride (PVDF), Solef 5130). The resulting slurry was dispersed in a planetary centrifugal mixer (ARE-250, Thinky Corp.; Japan), then the corresponding CAM was added, and the resulting mixture was dispersed again using the same apparatus as mentioned before to obtain a uniform slurry. Subsequently, the slurry was cast onto aluminum foil using a doctor blade technique. After drying, circular electrodes with a diameter of 1.4 cm were punched out and were heated at 120° C. for 10 min. -3The mass loading was adjusted to 15 mg / cm 2 .
[0219] III.2 Electrolyte Manufacturing
[0220] A matrix electrolyte composition (EL matrix 1) was prepared, which contained 12.7 wt% of LiPF6, 26.2 wt% of ethylene carbonate (EC) and 61.1 wt% of ethyl methyl carbonate (EMC) based on the total weight of EL matrix 1, and then 2 wt.% of vinylene carbonate (VC) was added to the matrix electrolyte formulation to obtain the final composition EL matrix 2, which was used for electrochemical evaluation of electrodes based on the present invention and comparative CAM.
[0221] III.3 Battery cell preparation and electrochemical evaluation
[0222] A button-type half-cell (20 mm in diameter and 3.2 mm in thickness) including a cathode as a working electrode and a lithium metal counter electrode prepared as described in III.1 was assembled and sealed in an Ar-filled glove box. In addition, the cathode and anode and the separator were stacked in the order of cathode / / separator / / Li foil to produce a half button cell. Thereafter, 0.15 ml of the EL matrix 2 described above (III.2) was introduced into the button cell.
[0223] Electrochemical testing of the aforementioned button cell cells was performed on a Maccor 4000 battery cycler with 3.0 and 4.7 V (4.8 V in the activation cycle (first cycle)) as the lower and upper cut-off voltages, respectively. After activation in the first cycle, C-rate testing was used to illustrate the rate capacity of the CAM in the range of 0.2-3C. After the C-rate testing, the electrodes were cycled at 0.5C in constant current constant voltage (CCCV) mode. Table 3 gives a detailed summary of the different C-rates of the test scheme.
[0224] Table 3: Overview of the electrochemical evaluation protocol used
[0225] cycle <![CDATA[C-rate charge / discharge a > model 1 0.067C CCCV 2 0.1C CCCV 4 Every 5% SOC DCIR 5 0.2C, 0.5C CCCV 9 0.5C / 1C CCCV 11 0.5C / 2C CCCV 13 0.5C / 3C CCCV 15 0.5C CCCV 17 Every 5% SOC DCIR 18 0.5C CCCV 69 Every 5% SOC DCIR 70 0.5C CCCV 121 Every 5% SOC DCIR
[0226] The stopping criteria for the constant voltage step in CCXCV mode is that the CV step lasts for 1 h or the total current reaches 0.02C.
[0227] Table 4: Summary of the electrochemical performance of the inventive CAMs (CAM.1, CAM.2) and comparative C-CAM.3.
[0228]
Claims
1. A method for manufacturing a (oxy)hydroxide of TM, where TM refers to a metal in which at least 97 mol-% is a transition metal, and where TM contains manganese and nickel, and where at least 50 mol-% of TM is manganese, the method comprising the following steps (a) providing an aqueous solution (α) of a water-soluble salt of at least one such metal and an aqueous solution (β) containing an alkali metal hydroxide selected from NaOH and KOH, (b) combining solutions (α) and (β) at a pH value in the range of 9.5 to 10.3, where step (b) is carried out using at least one coaxial mixer comprising two coaxially oriented pipes through which the aqueous solutions (β) and (α) are introduced into a stirring container, thereby precipitating the (oxy)hydroxide of TM, (c) recovering and drying the (oxy)hydroxide of TM.
2. The method according to claim 1, wherein: The outlets of these pipes of the coaxial mixer are below the liquid level.
3. A method according to any one of the preceding claims, wherein: The aqueous solution (α) is introduced through the inner pipe of the mixer, and the aqueous solution (β) is introduced through the outer pipe.
4. A method according to any one of the preceding claims, wherein: Between steps (b) and (c), step (b+) is carried out, which includes transferring the slurry from step (b) to a second stirring container where it is combined with solutions (α) and (β) at a pH value in the range of 9.5 to 11.0 measured at 23 °C, where step (c) is carried out in a continuous or semi-continuous mode, thereby enabling further growth of these (oxy)hydroxides of TM.
5. A method according to any one of the preceding claims, wherein: The drying in step (c) is carried out at a temperature in the range of 80 °C to 120 °C.
6. A method according to any one of the preceding claims, wherein: The water-soluble salts of manganese and nickel in step (a) are sulfates.
7. A method according to any one of the preceding claims, wherein: At certain time intervals, the nozzle is rinsed with water to physically remove the transition metal (oxy)hydroxide scaling.
8. A method according to any one of the preceding claims, wherein: TM contains a metal according to formula (I) No a M 1 b Mn c (AND) where the variables are each defined as follows: M 1 is at least one metal selected from the group consisting of Co, Ti, Zr, Nb, Ta, W, Sb, Sr, Al and Mg, a is a number in the range of 0.20 to 0.50, b is a number in the range of zero to 0.05, c is a number in the range of 0.50 to 0.80, and a + b + c = 1.
0.
9. A granular metal (oxy)hydroxide according to general formula (II) TMO x (OH) y (CO3) t (II) where TM refers to a combination of metals in which at least 97 mol-% is a transition metal, and where TM contains manganese and nickel, and where at least 50 mol-% of TM is manganese, 0 ≤ x < 1, 1 < y ≤ 2, and 0 ≤ t ≤ 0.1, where the granular transition metal (oxy)hydroxide has an average secondary particle diameter D50 in the range of 2 to 15 μm, and where such secondary particles are aggregated from primary particles that are substantially radially oriented.
10. The granular metal (oxy)hydroxide according to claim 9, wherein TM corresponds to the Ni a M 1 b Mn c Metal where M 1 is at least one metal selected from the group consisting of Co, Ti, Zr, Nb, Ta, W, Sb, Sr, Al and Mg, a is a number in the range of 0.20 to 0.50, b is a number in the range of zero to 0.05, c is a number in the range of 0.50 to 0.80, and a + b + c = 1.
0.
11. The granular metal (oxy)hydroxide according to claim 9 or 10, wherein The metal (oxy)hydroxide shows reflections at 8.6° to 9.0° (a), 16.00° to 18.00° (b), and 21.40° to 22.00° 2θ (c) in an X-ray diffraction analysis recorded using Cu-Kα radiation.
12. The particulate metal (oxy) hydroxide according to any one of claims 9 to 11, having a molecular weight of 2 to 50 m 2 The specific surface area according to BET is in the range of 1.1767 W / g.
13. The particulate metal (oxy)hydroxide according to any one of claims 9 to 12, wherein The particle size distribution [(D90)-(D10)] divided by (D50) is in the range of 0.5 to 2.
14. The particulate metal (oxy)hydroxide according to any one of claims 9 to 13, wherein The average shape factor of the secondary particles was above 0.80 when measured by SEM imaging at 1000× magnification.
15. Use of the particulate metal (oxy)hydroxide according to any one of claims 9 to 14 for the production of cathode active materials for lithium ion batteries.
16. A method for producing a cathode active material for a lithium ion battery, wherein the method comprises the following steps (1) mixing at least one metal (oxy)hydroxide according to any one of claims 9 to 14 with at least one lithium compound selected from lithium hydroxide, lithium carbonate and lithium peroxide and optionally at least one oxide or (oxy)hydroxide or sulfate of Mg, Al, Ti, Zr, Nb, Ta, W or Mo, and (2) The mixture obtained in step (1) is heated to 800°C to 1000°C.
17. A method according to the general formula Li 1+k TM 1-k A particulate cathode active material of O2, wherein k is in the range of 0.1 to 0.3, and wherein TM refers to a combination of metals of which at least 97 mol-% are transition metals, and wherein TM comprises manganese and nickel, and wherein at least 50 mol-% of TM is manganese, wherein the particulate cathode active material has an average secondary particle diameter D50 in the range of 2 to 15 μm, And wherein such secondary particles are aggregated from substantially radially oriented primary particles, and wherein such secondary particles have an average shape factor greater than 0.80 when measured by SEM imaging at 1000× magnification.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery, method for producing same, and lithium secondary battery
EP3486980A1